Towards an integrative framework of family guidance and counseling in children's educational psychology: A systematic literature review - Chandra Duwita Ela Pradana; Rani Ditia Ningsih; Maria Mistika Magho; Vendy Kurniawan; Muhamad Agung Febrianto (Eduvista: Journal of Education and Innovation, 2026)
Research on family guidance and counseling and children's educational psychology has developed rapidly. However, the relationship between these two fields has generally been examined separately, resulting in the absence of a comprehensive conceptual synthesis. This study aimed to analyze and synthesize the relationship between family guidance and counseling and children's educational psychology while developing an integrative conceptual framework. The study employed a Systematic Literature Review (SLR) following the PRISMA guidelines by reviewing 26 studies that met the inclusion criteria. The findings identified two major themes, namely preventive family support and collaborative family-based interventions, which operate by strengthening children's psychological resources, including self-efficacy, learning motivation, self-regulation, emotional regulation, and academic resilience. These psychological resources subsequently contribute to improved learning engagement, academic achievement, socio-emotional competence, student well-being, and mental health. This study contributes by proposing an integrative conceptual framework that strengthens the connection between family guidance and counseling and educational psychology while providing a theoretical foundation for developing more preventive and collaborative family-based interventions. Abstrak Perkembangan kajian bimbingan dan konseling keluarga serta psikologi pendidikan anak berlangsung pesat. Namun, keterkaitan kedua bidang tersebut masih cenderung dikaji secara terpisah sehingga belum tersedia sintesis konseptual yang komprehensif. Penelitian ini bertujuan menganalisis dan mensintesis hubungan antara bimbingan dan konseling keluarga dengan psikologi pendidikan anak serta mengembangkan kerangka konseptual yang integratif. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan mengikuti pedoman PRISMA terhadap 26 artikel yang memenuhi kriteria inklusi. Hasil penelitian mengidentifikasi dua tema utama, yaitu preventive family support dan collaborative family-based interventions, yang bekerja melalui penguatan sumber daya psikologis anak, meliputi efikasi diri, motivasi belajar, regulasi diri, regulasi emosi, dan resiliensi akademik. Sumber daya psikologis tersebut selanjutnya berkontribusi terhadap peningkatan keterlibatan belajar, prestasi akademik, kompetensi sosial-emosional, kesejahteraan siswa, dan kesehatan mental. Penelitian ini memberikan kontribusi melalui pengembangan kerangka konseptual integratif yang memperkuat hubungan antara bimbingan dan konseling keluarga dengan psikologi pendidikan sekaligus menjadi landasan teoritis dalam pengembangan intervensi keluarga yang lebih preventif dan kolaboratif.